Review of the effect of Erbium and Neodymium on microstructure and mechanical properties of aluminium alloy - Ahmad, Rosli; Abdul Rahman, Abdul Raziq (Research Progress in Mechanical and Manufacturing Engineering, 2021)
The application of aluminium alloy in automotive and aerospace industries has supported the need to study the effect of rare earth elements on alluminium alloys. In this study, the effect of the rare earth element erbium (Er) and neodymium (Nd) on the microstructure and mechanical properties of the Aluminium alloy was reviewed. The case study method was conducted by referring from previous researches and journal articles. In the selected references, from the experiments that were conducted using optical microscopy (OM), scanning electron microscopy coupled with electron dispersive spectroscopy, Tensile test and Vickers Hardness test showed that the addition of erbium and neodymium in different amounts improved the grain size, Ultimate Tensile Strength and hardness value of the aluminium alloys. Both additives improved the microstructure and mechanical properties of aluminium alloys but different types of aluminium alloys have different compositions which makes the optimum weight percentage of erbium and neodymium addition to differ too.